Evaluation and comparision of cognitive development in premature infants and full-term infants during early childhood - Paolini, Cynthia Inés (2018)
Premature infants have an increased risk of having long-term learning problems. However there is little information about the impact of prematurity on early cognitive development. Early detection of children with increased cognitive risk is relevant to prevent learning problems at more advanced ages. The aims of this research were to study delay in cognitive development in preterm infants and to compare cognitive development between premature and full-term infants during earlychildhood. Cross-sectional descriptive study design. Argentine scale of sensory motor intelligence (EAIS) was administered to assess cognitive development. Frequency of cognitive delay was studied in preterm and full term infants. The risk of cognitive difficulties by degree of prematurity, compared with term infants was calculated. A total of 232 preterm and 214 term infants, were evaluated. Thefrequency of cognitive impairments in premature infants was higher (26.7%) than in term infants (14.5%). This difference was statistically significant (p value=0.004). The risk of delay in cognitive development increases with decreasing gestational age, but late preterm infants also are at higher risk of cognitive delay than those born at term. Gestational age (GA), birth weight (BW), intrauterine growth retardation (IUGR) and neonatal complications are risk factors for early cognitivedevelopment. We found that preterm infants have almost 3 times more chance of retarded cognitive development than a full-term infants (OR=2.80 [IC95% 1.56-5.0]; p<0.001). This probability tends to increase as gestational age decrease. Premature infants less than 32 weeks of gestation are almost 5 times more likely to have a delay in cognitive development than those born at term(OR=4.88 [IC95%:2.36-10.09]; p<0.001). Prematurity produces an impact on cognitive development that can be detected during early childhood. The difficulties are greater with decreasing GA, BW, IUGR and with neonatal complications, without neglecting the importance of monitoring also late preterm.